Implementation of Right to Information Act in Government Institutions: A Study Based on Jaffna District - Raguram, S.; Dhulabarani, M. (Faculty of Management Studies and Commerce, University of Jaffna, 2020)
The Right to Information (RTI) act globally is considered as an instrument that provides rights to the public and ensures transparency and accountability of general authorities. Public access to information is viewed as a key to public participation in democracy. After long deliberation, the right to information act was included in the constitution of Sri Lanka on May 15, 2015, and made law through the 19th amendment to the constitution. Thereafter, this was passed as Act No. 12 of 2016 in June 2016. The Act is considered one best of its kind across the world. However, even after four years in the enactment in enactment, the implementation of the RTI Act is faced with a lot of challenges. Particularly, it is observed that the proposed appointment of information officers at all the government offices is still not implemented properly. The implementation of this Act has many limitations in government offices. Even though sufficient awareness exists among government officers regarding this Act, many parties observe that the government officers do not pay due attention to the Act in regular work affairs. The power structure and mechanisms to provide information to the public are not properly established in many government offices. In this situation, these offices do not provide information to the public voluntarily. Lack of full swing support from the Right to Information Commission to the implementation of this act learned to be one of the reasons for this situation. The situations explored above were observable only after the introduction of this Act in Sri Lanka. There is an ongoing deliberation regarding the reasons for these situations. Hence, it is necessary to assess the levels of effort made by the government organizations to the efficient implementation of the Right to Information Act in Sri Lanka. The objective of the study is to explore vital research questions such as: to what extent the Right to Information Act has been implemented in Sri Lankan government offices; what are the mechanisms used to provide information; what arrangements are in place to provide information and to implement Right to Information Act; is there sufficient numbers of Information Officers available to ensure the efficient implementation of the act; are electronic means used to store the data; how the Right to Information Commission functions in these aspects, how the existing laws and behaviours of government officers affect the implementation of Right to Information Act, and to what extent the government offices disclose information to the public in proactively. In this respect, this study used quantitative analysis as the research method. Details of Information requests forwarded by the public to important government offices in the Jaffna District: District Secretariat, Nallur Divisional Secretariat within one period were gathered. The details regarding subsequent steps taken in respect to these requests were collected from information officers. Interviews and discussions were conducted with Information Officers. Based on collected data and information, it was concluded that the implementation of the Right to Information Act remains in its infancy. This is the case not only with District level government offices but also in Divisional level offices. This study exposed the kinds of drawbacks associated with the implementation of the Right to Information Act.
Keywords: Right to Information Act; Government Institutions; Law Enforcement